The Effect of the Plyometric Method on the Accuracy of Student Kicks in Extracurricular Football : Pengaruh Metode Plyometric Terhadap Ketepatan Tendangan Siswa di Ekstrakurikuler Sepak Bola - Safarudin; Jeane Betty Kurnia Jusuf (Wadah Inovasi Indonesia, 2023)
This study was conducted to see whether there is an influence of the plyometric training method on the accuracy of student kicks and how much the influence of the plyometric training method on the accuracy of student kicks. The research was carried out with pretest and post test experimental methods. The number of subjects amounted to 30 people. Data retrieval using a kicking skills test instrument. The analysis technique uses normality test, homogeneity test, and hypothesis test (T test). The results of the study found that the pliometric training method had an influence on the accuracy of kicks and the pliometric training method significantly affected students' kicks. The benefit of this research is that it is a reference source for workable soccer training programs